Composite grid structure technology for space applications. (2021) - Giusto, G.; Totaro, G.; Spena, P.; De Nicola, F.; Di Caprio, F.; Zallo, A.; Grilli, A.; Mancini, V.; Kiryenko, S.; Das, S.; Mespoulet, S.
Abstract: This paper presents the general aspects of the technological development of three applications in composite Grid structure for payloads and launch vehicles, within the framework of ESA projects. Two applications are devoted to payloads structures, that is, a central tube for medium-class satellite platforms and a boom segment for deployable antennas, whereas the third application concerns the conical interstage 2/3 of the new European launcher VEGA C, that CIRA is developing in partnership with Avio, whose qualification phase is currently in progress. The paper discloses part of the development activities of the mentioned Grid structures, including the preliminary design approach and the material selection criterion that are integrated with a patented deposition process based on dry Filament Winding and resin liquid infusion. This overall technology development, in light of the different readiness levels and goals of respective projects, has proven the possibility to provide highly efficient and low cost solutions for primary Grid structures with various design requirements and dimensions of the shell.